PENGARUH BELLY DANCE DIKOMBINASIKAN DENGAN PIJAT ENDORPHIN TERHADAP PENGURANGAN RASA NYERI PADA IBU BERSALIN KALA 1 - Lumbantobing, Hendri Parluhutan; Sinaga, Renny; Sianipar, Kandace (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2020)
Physiologically, all women who give birth will experience pain during labor process and statistically, labor pain cannot be tolerated by two out of three mothers. Women who get massages during labor will experience a significant decrease in anxiety, reduction in pain, and shorter delivery time. No wonder that endorphin massage technique is important to be mastered by pregnant women and husbands who enter the gestational age of the 36th week. The second thing that can be done to deal with the labor pain besides the endorphin massage is dancing. Dancing is a performance art but also can heal and free someone, especially the pregnant women who suffer from psychological disorders. The purpose of this study was to determine the effect of belly dance combined with endorphin massage in reducing pain in the first stage of labor at the Beringin Health Center Tapian Dolok District, Simalungun Regency. The hypothesis in this study was belly dance and endorphin massage were effective in reducing pain in primiparous mothers. The type of this research was a quasi-experiment. The design of this study was pre and post-test design. The required number of samples was 16 + 1.6 = 17.6 or n = 18 samples, that was the sample size for the control group was 18 samples and the sample size for the treatment group was 18 samples, so the total number of samples needed in this study were n = 36 respondents. The results showed that there was an effect of endorphin massage combined with belly dance (asymp.sig 0.004) on reducing pain in first stage of labor. This study is expected to provide an education to pregnant women about the importance of the belly dance combined with endorphin massage in reducing pain in first stage of labor, so that pregnant women can do a belly dance combined with endorphin massage at home.